Sitting anthropometries of primary school children in the rural and urban areas in Pahang / Hanani Yuhaniz …[et al.] - Yuhaniz, Hanani; Seraila, Asnawi; Muhammed, Suhaimi; Saleh, Abdul Hamid (2015)
Anthropometries which means body measurements comes from one of the factors in ergonomics. Ergonomics is important to ensure humans perform efficiently. In this study, anthropometries of 600 primary school children from rural and urban areas were taken to analyse the differentiation of sizes among the two provinces. The state of Pahang was chosen for this study as it is the biggest state in Peninsular Malaysia. Gathering anthropometries data enable designers to make different sizes of furniture to certain areas to meet the requirements of ergonomics. It is found that there are significant differences in anthropometrics between the rural and urban areas.